From emotional intelligence to suicidality: a mediation analysis in patients with borderline personality disorder - Mohsen Khosravi; Fahimeh Hassani (BMC Psychiatry, 2022)
Abstract Background Borderline personality disorder (BPD) is a serious mental illness with a high suicidality rate between 40 and 85%. However, little is known concerning psychosocial risk and protective factors associated with suicidal behaviors in this clinical group. The main focus of the present study was on examining the relationship of emotional intelligence (EI) with suicidal behaviors and its mediators (e.g., depression, self-esteem, addiction potential, and disorder severity) among patients with BPD. Methods In this cross-sectional study, a total of 220 participants (including 110 patients with BPD and 110 healthy controls) in Zahedan, Iran, were examined using clinical interviewing and self-report measures of EI, suicidal behaviors, depression, self-esteem, addiction potential, and BPD symptom severity. The data were analyzed using SPSS v25.0 software at the significance level of p < 0.05. Results Our preliminary analysis showed higher levels of EI, depression, and self-esteem in the BPD group in comparison to healthy controls (p < 0.001). Furthermore, our findings showed that higher levels of addiction potential, BPD symptom severity, and depression and lower levels of self-esteem and EI were likely to be related to suicidal behaviors of the BPD group. Our results also supported the overall hypothesis that addiction potential, depression, BPD symptom severity, and self-esteem had a mediating role in the impact of EI on suicidal behaviors in the BPD group. Conclusions According to these findings, we have come to believe that training EI possibly plays a directly and/or indirectly potential preventive and therapeutic role in suicidal behaviors among patients with BPD. However, further longitudinal studies must be carried out to clarify the cause and effect relationship between EI, depression, self-esteem, addiction potential, BPD symptom severity, and suicidal behaviors.